Microwave hydrothermal synthesis and luminescent properties of ZnWO₄ nanoparticles - Yakubovskaya, A.; Tupitsyna, I.; Sofronov, D.; Vovk, O.; Katrunov, K.; Zhukov, A.; Baumer, V.; Andrushchenko, A. (Functional Materials, 2013)
Nanosized crystals of zinc tungstate were synthesized by microwave-hydrothermal method under different conditions of temperature and pH of initial solutions. Emergence of the nanophase was established in temperature range of the microwave processing from 120°C to 200°C. Change in the morphology of the crystallites synthesized at 120–200°C and 6 ≤pH ≤10 units were considered. Transformation of the nanograins (size of 10 nm to 40 nm) to nanorods (length of 50 nm to 200 nm) and their enlargement occurs when temperature of the microwave processing and pH of the initial solutions rise. The relation between luminescent parameters of the nanocrystals and their morphological features was investigated.